2015
DOI: 10.12968/jowc.2015.24.sup4a.s12
|View full text |Cite
|
Sign up to set email alerts
|

A 9-year retrospective evaluation of 102 pressure ulcer reconstructions

Abstract: The authors have no conflicts of interest to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
13
1
1
Order By: Relevance
“…Ulcer recurrence and wound dehiscence are the most common surgical complications with recurrence rates as high as 80% in some series. 12 , 13 , 16 , 17 , 19 21 The wide variation in reported outcomes suggests that patient-specific risk factors should be investigated further to determine the optimal operative settings. We hypothesized that there are patient-specific and potentially modifiable risk factors associated with complications after flap reconstruction for pressure ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Ulcer recurrence and wound dehiscence are the most common surgical complications with recurrence rates as high as 80% in some series. 12 , 13 , 16 , 17 , 19 21 The wide variation in reported outcomes suggests that patient-specific risk factors should be investigated further to determine the optimal operative settings. We hypothesized that there are patient-specific and potentially modifiable risk factors associated with complications after flap reconstruction for pressure ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…In the other prediction models constructed in this study, haemoglobin emerged as an influential factor in addition to HCT and RBC. Low HCT and haemoglobin levels indicate anaemia, a chronic disease that almost certainly contributes to delayed wound healing in PI (Kenneweg et al, 2015). For example, a retrospective cohort study by Takahashi et al (2009) showed that the number of wounds and haemoglobin levels remained significant predictors of healing status in adults with chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia is traditionally associated with poor nutritional status and subsequent high incidence of postoperative complications, including wound dehiscence and ulcer recurrence. 32 Recent evidence has shown that this nutritional marker alone is inadequate as an independent predictor of complications in pressure sore patients. 33 Serum albumin levels may be affected only in those experiencing “extreme” starvation (defined as a body mass index <12 kg/m 2 ) or greater than 6 weeks’ starvation.…”
Section: Methodsmentioning
confidence: 99%